Non-pharmacological Therapy for the Elderly to Prevent Dementia through Cognitive Stimulation Therapy: A Systematic Review - Martha Lowrani Siagian; Retno Indarwati; Pudji Lestari (Universitas Airlangga, 2020)
Introduction: Dementia is the most prevalent disease in older people and it has become the largest global public health priority. Not only does it cause a progressive loss of independent functioning, a decline in the cognition of people with dementia and family restlessness but it also leads to an enormous social and economic burden. The aim of this study was to describe the non-pharmacological therapy that is commonly used and to show the significantly effect that it has in terms of preventing cognitive decline in the elderly with dementia.Methods: The literature review approach was used with a cross-sectional framework. Data was taken using a checklist and observations that were modified from the key words used to search Scopus databases. The 20 final articles were published from 2010 to 2019. The data was analyzed through a comparative studyResults: There are several interventions based on cognitive stimulation therapy including clock-drawing, board games, story-telling, musical therapy, bright light therapy, aromatherapy, touch therapy, gardening, brain gym, modality therapy etc. From the study, it was found that cognitive stimulation therapy is suitable in all conditions, is easy to implemented and it significantly improved the cognitive and executive functioning of the elderly with dementia.Conclusion: Nowadays, most studies concern alternative approaches that are non-invasive, cost-effective, safe and easy to implement. Cognitive stimulation therapy can be the best choice. It is expected that further research is needed to find other tools for scoring the intervention that is most suitable for all.